Periodical structure of vortices in a semiconductor single wafer spin cleaner - Toshinori KOUCHI; Naoya FUKUDA; Yusuke NAKANO; Yoshiya SHIMIZU; Yasunori NAGATA; Shinichiro YANASE (Nihon Kikai Gakkai ronbunshu, 2015)
We experimentally and numerically investigated large-scale structures formed by vortices in a single wafer spin cleaner. The Q-criterion identified the vortices developed in the cleaner as the flow regions with positive second invariant of the velocity gradient tensor obtained by both the PIV and LES. The time-series two-components PIV data shows that small-vortices were clustered near and under the edge of the rotating disk and were periodically emanated from there to the housing wall of the cleaner. The emanation frequency was increased with increasing in the angular velocity of the rotating disk. Three-dimensional LES reveal that six longitudinal vortices were spirally developed from under the edge of the rotating disk to the housing wall. This structure stably rotated slower than the disk speed. Fourier analysis of the LES data agreed with that of the PIV data. This supports that the passages of the stable spiral vortices on the PIV measurement region resulted in the periodical emanation of the clustered small-vortices observed in the PIV. Such a very large-scale spiral structure will induce reattachment of contaminants on the wafer surface, and should be destructed for development of much higher efficient cleaner.